PERBEDAAN TRANSPOR MUKOSILIAR SEBELUM DAN SESUDAH TERAPI LARUTAN HIPERTONIK DAN ISOTONIK PADA PASIEN RINOSINUSITIS KRONIK - RISFA INDRISEFANI; SITI MASLIANA SIREGAR (JURNAL ILMIAH KOHESI, 2021)
Nasal and paranasal sinus inflammation can interfere with the function of mucociliary transport which is a local defensemechanism of the nose and paranasal sinuses. The use of hypertonic and isotonic solutions as nasal wash therapy inchronic rhinosinusitis is still controversial. This study aims to find out the differences of mucociliary transport before and aftertherapy of hypertonic and isotonic solutions in patients with chronic rhinosinusitis. This was a pure experimental study withrandomized control trial pre and post designs. Data is processed using the SPSS Mann-Whitney test. The results showedthat differences in mucociliary transport before and after therapy of hypertonic and isotonic solutions in patients with chronicrhinosinusitis showed a p value of 0.001 (p <0.05). There is a difference in mucociliary transport time before and afterhypertonic solution therapy with a greater decrease in time than isotonic solution in patients with chronic rhinosinusitis.